2006
DOI: 10.1007/s10286-006-0305-z
|View full text |Cite
|
Sign up to set email alerts
|

Plasma catecholamines and blood volume in native Andeans during hypoxia and normoxia

Abstract: Plasma catechols and blood volume were measured in 20 male, native high-altitude residents of Cerro de Pasco, Peru (4338 m), while hypoxic and subsequently while normoxic at sea level. Ten subjects were healthy controls,with hematocrits lower than 61%, and ten had chronic mountain sickness (CMS), a syndrome of maladaptation to altitude, characterized by polycythemia (hematocrit > 61%), profound hypoxemia, and neurologic symptoms. The main aim of the study was to evaluate the chronic effects of hypoxia on plasm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
1

Year Published

2007
2007
2016
2016

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(16 citation statements)
references
References 32 publications
1
14
1
Order By: Relevance
“…Arterial wall stiffness is greater and blood pressures are higher [51, 52]. High altitude residents, both healthy subjects and patients with chronic mountain sickness (see below) have higher catecholamine levels when measured at altitude than following descent to sea level [20]. Baroreceptors, however, appear to function normally at altitude [5].…”
Section: Autonomic Function In High Altitude Residentsmentioning
confidence: 99%
“…Arterial wall stiffness is greater and blood pressures are higher [51, 52]. High altitude residents, both healthy subjects and patients with chronic mountain sickness (see below) have higher catecholamine levels when measured at altitude than following descent to sea level [20]. Baroreceptors, however, appear to function normally at altitude [5].…”
Section: Autonomic Function In High Altitude Residentsmentioning
confidence: 99%
“…Occasionally, this position is supported by the results of studies in recent years [70][71][72]. But over the past decade, a number of studies received the data which are contrary to this popular point of view [73][74][75][76]. So, Otsuka K et al [75] showed higher diastolic pressure and thicker walls of arteries in highaltitude residents (Leh, Ladakh) compared with sea-level residents.…”
Section: Hypertension Risk Of Acute Mountain Sickness and Other Advmentioning
confidence: 74%
“…Gamboa et al [ 111 ] reported higher plasma levels of noradrenaline, dopamine and the noradrenaline metabolite dihydroxyphenylglycol (DHPG) in Andeans at their resident altitude compared to data obtained following descent to sea level, suggesting sympathetic activation at altitude. Other studies suggest that, unlike following acute exposure to hypoxia where there is down-regulation of β -adrenoceptors in response to sympathetic overactivity [ 86 ], in Andeans chronically exposed to hypoxia there is no such change [ 116 ], and no evidence for adrenergic desensitivity in either healthy altitude dwellers or those with CMS.…”
Section: Changes In Catecholamine Levelsmentioning
confidence: 94%
“…Heart rate is signifi cantly higher in altitude dwellers at their resident altitude than following descent to sea level [ 109 ]. This effect is more pronounced in those with CMS who also have increased arterial wall stiffness [ 110 ], increased circulating catecholamine levels, particularly noradrenaline [ 111 ] and altered barorefl ex control (see below). This tendency to higher blood pressures and sympathetic activation may predispose to the increased cardiovascular morbidity in these populations.…”
Section: Effects On the Cardiovascular Systemmentioning
confidence: 97%